Inflow cannula position as risk factor for stroke in patients with HeartMate 3 left ventricular assist devices. Issue 6 (9th January 2022) - Schlöglhofer, Thomas; Aigner, Philipp; Migas, Marcel; Beitzke, Dietrich; Dimitrov, Kamen; Wittmann, Franziska; Riebandt, Julia; Granegger, Marcus; Wiedemann, Dominik; Laufer, Günther; Moscato, Francesco; Schima, Heinrich; et al.
Abstract: Background: A relation between the left ventricular assist device inflow cannula (IC) malposition and pump thrombus has been reported. This study aimed to investigate if the pump position, derived from chest X‐rays in HeartMate 3 (HM3) patients, correlates with neurological dysfunction (ND), ischemic stroke (IS), hemorrhagic stroke (HS) and survival. Methods: This analysis was performed on routinely acquired X‐rays of 42 patients implanted with a HM3 between 2014 and 2017. Device position was quantified in patients with and without ND from frontal and lateral X‐rays characterizing the IC and pump in relation to spine, diaphragm or horizontal line. The primary end‐point was freedom from stroke and survival one‐year after HM3 implantation stratified by pump position. Results: The analysis of X‐rays, 33.5 (41.0) days postoperative, revealed a significant smaller IC angle of HM3 patients with ND versus no ND (0.1° ± 14.0° vs. 12.9° ± 10.1°, p = 0.005). Additionally, the IC angle in the frontal view, IS: 4.1 (20.9)° versus no IS: 13.8 (7.5)°, p = 0.004 was significantly smaller for HM3 patients with IS. Using receiver operating characteristics derived cut‐off, IC angle <10° provided 75% sensitivity and 100% specificity (C‐statistic = 0.85) for predicting IS. Stratified by IC angle, freedom from IS at 12 months was 100% (>10°) and 60% (<10°) respectively ( p = 0.002). No significant differences were found in any end‐point between patients with and without HS. One‐year survival was significantly higher in patients with IC angle >10° versus <10° (100% vs. 71.8%, p = 0.012). Conclusions: IC malposition derived from standard chest X‐rays serves as a risk factor for ND, IS and worse survival in HM3 patients. Abstract : Inflow cannula malposition (inflow cannula angle <10°) derived from standard chest X‐rays serves as a risk factor for neurological dysfunction, ischemic stroke and worse survival in HeartMate 3 patients.